The effects of market-oriented farming on living standards, nutrition, and informal sharing arrangements of smallholder farmers: the case of African indigenous vegetables in Kenya - Christoph Kubitza; Sarah Hackfort; Arnold Opiyo; Cornelia Rauh; Caroline S. Stokes; Susanne Huyskens-Keil (Food Security, 2024)
The shift from subsistence to more market-oriented agriculture is viewed as essential to increase smallholder farmers' welfare. However, its impact on farmers' nutrition and informal sharing arrangements and associated solidarity within African farming communities remains uncertain. To analyse these trade-offs, we study the growing commercialization of African indigenous vegetables (AIV) in Kenya. These vegetables are an essential component of local diets in rural areas but also of informal sharing arrangements that provide access to food outside of markets. This article combines quantitative data from a 2016–2022 panel survey of farmers with qualitative data from focus group discussions. Results based on household fixed-effects models show a significant increase in households' non-food expenditures due to selling AIV. The results suggest that selling AIV did not negatively affect nutrition outcomes but did not improve them either. Informal AIV sharing between households decreased further with growing market participation. Panel data models indicate, however, inconsistent and insignificant changes in associated solidarity indicators. We attribute this to the multiple and sometimes opposing effects of market-oriented farming on solidarity, as revealed by focus group discussions. While some farmers perceive reduced solidarity due to less informal AIV sharing, others perceived this traditional solidarity to be partially forced. Other forms of social interaction have also emerged, such as cooperatives and more intensive knowledge sharing. Despite concerns about the loss of informal sharing and community solidarity and limited improvements in nutrition outcomes, the tangible income gains generated by selling AIV are likely to foster further growth in the AIV sector.
Keywords: 630; Smallholder farmers; African indigenous vegetables; Commercialization; Mixed methods